Tracking the quality of a biomedical/clinical engineering unit using statistical process control - Türegün, K. Dilara. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2009., 2009)
Since, healthcare is an ever-changing environment, it is vital for each institution to be prepared to face and consequently conquer technological future advancements in medicine. This can be accomplished by careful selection of appropriate indicators which are essential to measure the performance and quality of processes and their improvements. Statistical process control (SPC) is a key approach to quality improvement. Control charts, central to SPC, are used to visualize and analyze the performance indicators over time. In this study, SPC principles were incorporated into .NET Framework on MS Windows to design and develop a control system for biomedical engineering departments in hospitals. With the use of the software developed, biomedical/clinical engineering departments' processes were analyzed using real time SPC techniques (X control chart and Cusum control chart), which permitted monitoring, controlling and improving the implementation of di erent quality and performance indicators through analysis. This expert system enables the user to be noti ed of any potential problems, just in time to implement various techniques for their improvement.|Keywords: Biomedical Engineering, Quality Indicators, SPC, CUSUM.
Keywords: Biomedical engineering.; Process control -- Statistical methods.; CUSUM technique.